Potato peels waste as a sustainable source for biotechnological production of biofuels: Process optimization - Rodríguez-Martínez, Beatriz (2023)
Potato peel waste (PPW) is a starchy by-product generated in great amounts during the industrial processing of potatoes. It can be used as a low cost alternative, and renewable feedstock for the production of second generation bioethanol. In order to intensify this process, Saccharomyces cerevisiae Ethanol Red®, a robust and thermotolerant yeast strain, was selected and two experimental designs and response surfaces assessment were conducted to enable very high gravity fermentations (VHGF) using PPW as feedstock. The first one focused on the optimization of the liquefaction and enzymatic hydrolysis stages, enabling a maximum ethanol concentration of 116.5 g/L and a yield of 80.4 % at 72 h of fermentation; whereas, the second one, focus on the optimization of the pre-saccharification and fermentation stages, which further increased process productivity, leading to a maximum ethanol concentration of 108.8 g/L and a yield of 75.1 % after 54 h of fermentation. These results allowed the definition of an intensified pre-saccharification and simultaneous saccharification and fermentation (PSSF) process for ethanol production from PPW, resorting to short liquefaction and pre-saccharification times, 2 h and 10 h respectively, at an enzyme loading of 80 U/g PPW of Viscozyme and 5 UE/g PPW of SAN Super and a higher fermentation temperature of 34 °C due to the use of a thermotolerant yeast. Overall, with these conditions and solely from PPW without any supplementation, the outlined PSSF process allowed reaching a high ethanol concentration and yield (104.1 g/L and 71.9 %, respectively) standing at high productivities with only 54 h of fermentation.